The Danggit Processing Livelihood Project in Prieto Diaz, Sorsogon, A Fish CORAL Project in Gulf Albay - De Leon, Ramon T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The Bureau of Fisheries and Aquatic Resources (BFAR) rolled-out the Dangit Processing Livelihood FishCORALProject for the fishers’ organization in Prieto Diaz, Sorsogon in mid 2019 funded by UN-IFAD. Designed to help reduce poverty through increased household income, women participation and project sustainability. This study looked into the relevance, effectiveness and efficiency of implementation and readiness in attaining project objectives. The study is mixed descriptive method and used semi-structured questionnaire, key informants interview, FGD and secondary data analysis. The project was found relevant but poor in coordination and involvement of other stakeholders. Effective but failed to contribute to poverty reduction due to late implementation, no comprehensive project plans and technical support. Inefficient as it failed to translate resources it to incomes and sustained operations. The community organizationsare not ready and capable (lack technical and business management skills). The local resources (danggit, people and community organization) guarantee sustainability if managed appropriately. Women empowerment is hardly achieved. Recommendations;1) Develop project sustainability plan (technical and business facets of theproject), capacitate the organization along leadership and business management. 2) Bio-ecological data be produced on danggit stock to fine tune harvesting and regenerative capacity to ensure sustainability of supply. 3) Technical support provision coming from BFAR, LGU, academe, DTI, DOST, NLRC, NGOs in the form of product development, value adding, branding & packaging, business management, access to funds, assigning a full-time community facilitator as priority. Responsibilities and commitments of BFAR, LGU and the beneficiary be concretized through a memorandum of cooperation.